PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Sektor Properti dan Real Estate Di Bursa Efek Indonesia) - Nurazmi; Wardhiah; Jummaini; Marzuki (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2025)
This research aims to determine and analyze the influence of investment decisions, funding decisions and profitability on company value in the property and real estate sector listed on the Indonesia Stock Exchange. The data used in this research is time series data for the 2019-2023 time period and cross-section data sourced from 56 property and real estate sector companies on the Indonesia Stock Exchange. The analytical method used in this research is panel data regression using the eviews 12 analysis tool. Panel data regression estimation technique using the Common Effect, Fixed Effect and Random Effect models, based on the results of the Chow test and Hausman test and lagrage multiplier (LM) the results show that the Random Effect Model is appropriate to this research. The research results show that investment decisions (PER) and profitability (ROE) have a negative effect on company value, while funding decisions (DER) have a positive and significant effect on company value in property and real estate sector companies listed on the Indonesia Stock Exchange. Keywords : Investment Decisions, Funding Decisions, Profitability, Value Company